FUTURE PROSPECTS OF ROOF TOP SOLAR SYSTEM IN KERALA - Varghese, Jiju; Kumari, Dr. P. Saritha; F. Cleedin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines consumers’ satisfaction with rooftop solar system across different income group, utilizing an Analysis of Variance (ANOVA) approach. Data was collected from 150 consumers residing in Kollam District. Six factors are used to identify the level of satisfaction are efficiency, environmental benefits, after service, aesthetic looks, government subsidies and promotional efforts. The analysis revealed income level have significant impact on satisfaction level. It indicates that higher income groups are more satisfied on the efficiency, environmental benefits, after service and aesthetic looks of rooftop solar system. Whereas two factors not affected by income level are government subsidies and promotional efforts. These findings suggest that income plays a crucial role in shaping consumer’s satisfaction with rooftop solar. For analysis the statistical software SPSS is used. The study highlights the need for tailored strategies to enhance consumer satisfaction across all income groups, ensuring that the benefits of the Rooftop Solar System are equitably distributed.